PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA LOGISTIK BERBASIS WEB (STUDI KASUS PT. SOS INDONESIA) - Arpani; Entis Sutrisna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
With the development of technology that is growing so rapidly, companies are required to be able to follow the development of information systems that exist today. So that the information needed by a company in carrying out its operations can run well. PT. SOS Indonesia is one of the companies engaged in the field of human resources, one of which is in the field of parking management. In its operations, the logistics department does not only function as a support for the company's operations, but can increase the effectiveness and efficiency in the company's operational services. This research was conducted in order to help operational services in the logistics sector more easily streamline time, energy, costs in making reports and data collection logistics at each company location. Based on the data obtained by means of observation and interviews, then the data will be analyzed to create a programming design that fits the needs.